Penguatan Kesiapan Mental Atlet Tenis Lapangan Kab. Pangkep Melalui Pelatihan Self-Talk Berbasis Experiential Learning - Muflih Wahid Hamid; Nukhrawi Nawir; Tri Angriawan; Reza Mahyuddin; Muhammad Sadlzali (PT. Mediatama Zayna Indonesia, 2026)
This community service program aimed to enhance the mental readiness of tennis athletes from Pangkajene and Kepulauan Regency through an experiential learning-based self-talk training. Although the athletes possessed good technical skills, they still struggled to manage emotions, maintain focus, and cope with competitive pressure. The activity was carried out in two main stages: a socialization session emphasizing the importance of mental strengthening, and a self-talk training conducted through a competitive group game requiring participants to communicate only with positive words. Post-activity reflections revealed that the athletes developed greater awareness of the importance of focusing on their own abilities, maintaining composure in critical situations, and using positive communication within the team. The direct experiential approach helped them understand how positive thinking and language directly influence concentration and coordination. This training effectively fostered self-awareness, emotional regulation, and focus control, providing a practical, psychology-based mental development model that can be applied to the training of young athletes at the regional level.